Kontradiktif Perkawinan Beda Agama Perspektif Undang-Undang Perkawinan dan Undang-Undang Administrasi Kependudukan - Ditta Giarni Martha (Jurnal Indragiri Penelitian Multidisiplin, 2024)
This research aims to examine the philosophical basis for the formation of the Marriage Law and the Population Administration Law in regulating interfaith marriages. This research uses a method using study literature, namely a method by collecting data from previous research results regarding interfaith marriages and processing the data to analyze it on the philosophical basis of the Marriage Law and the Population Administration Law. The results of this research show that in the Marriage Law the existence of the Marriage Law jo. Government Regulation no. 9 of 1975. Article 2 paragraph (1) of the Marriage Law clearly stipulates that: "Marriage is valid if it is carried out according to the laws of each respective religion and belief." This means that a marriage can be categorized as a valid marriage if it is carried out according to the laws of each religion and belief of the couple entering into the marriage. Meanwhile, in the Population Administration Law, the philosophical basis is based on the Pancasila philosophy and the 1945 Constitution. The state has an obligation to provide protection and recognition for the determination and personal status and legal status of population law events and important events experienced by Indonesian citizens in the region or outside the region. Indonesia.